Development of individual competencies and team performance in interprofessional ward rounds: results of a study with multimodal observations at the Heidelberg Interprofessional Training Ward - Mitzkat, Anika; Mink, Johanna; Arnold, Christine; Mahler, Cornelia; Mihaljevic, André Leopold; Möltner, Andreas; Trierweiler-Hauke, Birgit; Ullrich, Charlotte; Wensing, Michel; Kiesewetter, Jan (Frontiers in medicine, 2023)
IntroductionInterprofessional training wards (IPTW) aim to improve undergraduates' interprofessional collaborative practice of care. Little is known about the effects of the different team tasks on IPTW as measured by external assessment. In Heidelberg, Germany, four nursing and four medical undergraduates (= one cohort) care for up to six patients undergoing general surgery during a four-week placement. They learn both professionally and interprofessionally, working largely on their own responsibility under the supervision of the medical and nursing learning facilitators. Interprofessional ward rounds are a central component of developing individual competencies and team performance. The aim of this study was to evaluate individual competencies and team performance shown in ward rounds.MethodsObservations took place in four cohorts of four nursing and four medical undergraduates each. Undergraduates in one cohort were divided into two teams, which rotated in morning and afternoon shifts. Team 1 was on morning shift during the first (t0) and third (t1) weeks of the IPTW placement, and Team 2 was on morning shift during the second (t0) and fourth (t1) weeks. Within each team, a tandem of one nursing and one medical undergraduate cared for a patient room with three patients. Ward round observations took place with each team and tandem at t0 and t1 using the IP-VITA instrument for individual competencies (16 items) and team performance (11 items). Four hypotheses were formulated for statistical testing with linear mixed models and correlations.ResultsA total of 16 nursing and medical undergraduates each were included. There were significant changes in mean values between t0 and t1 in individual competencies (Hypothesis 1). They were statistically significant for all three sum scores: “Roles and Responsibilities”, Patient-Centeredness”, and “Leadership”. In terms of team performance (Hypothesis 2), there was a statistically significant change in mean values in the sum score “Roles and Responsibilities” and positive trends in the sum scores “Patient-Centeredness” and “Decision-Making/Collaborative Clinical Reasoning”. Analysis of differences in the development of individual competencies in the groups of nursing and medical undergraduates (Hypothesis 3) showed more significant differences in the mean values of the two groups in t0 than in t1. There were significant correlations between individual competencies and team performance at both t0 and t1 (Hypothesis 4).DiscussionThe study has limitations due to the small sample and some sources of bias related to the external assessment by means of observation. Nevertheless, this study offers insights into interprofessional tasks on the IPTW from an external assessment. Results from quantitative and qualitative analysis of learners self-assessment are confirmed in terms of roles and responsibilities and patient-centeredness. It has been observed that medical undergraduates acquired and applied skills in collaborative clinic reasoning and decision-making, whereas nursing undergraduates acquired leadership skills. Within the study sample, only a small group of tandems remained constant over time. In team performance, the group of constant tandems tended to perform better than the group of random tandems. The aim of IPTW should be to prepare healthcare team members for the challenge of changing teams. Therefore, implications for IPTW implementation could be to develop learning support approaches that allow medical and nursing undergraduates to bring interprofessional competencies to team performance, independent of the tandem partner or team.